2017
DOI: 10.3390/rs10010018
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Coral Bleaching Using Temperature and Light: Progress towards an Operational Algorithm

Abstract: Abstract:The National Oceanic and Atmospheric Administration's Coral Reef Watch program developed and operates several global satellite products to monitor bleaching-level heat stress. While these products have a proven ability to predict the onset of most mass coral bleaching events, they occasionally miss events; inaccurately predict the severity of some mass coral bleaching events; or report false alarms. These products are based solely on temperature and yet coral bleaching is known to result from both tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 55 publications
4
84
0
Order By: Relevance
“…By the end of the 7-day heat stress event, ambient corals had experienced 2.5 DHW and warm-acclimated corals had experienced 4.5 DHW (conditions classified as "likely" to cause bleaching by NOAA), yet the light levels during the experiment were relatively low (arising from an abnormal period of cloudy weather; Figure 1C). Since temperature and light are synergistic stressors of coral bleaching, it is possible that the low light conditions that prevailed during the experiment alleviated the impact of the 4.5 DHW treatment to some extent (Skirving et al, 2018). While unexpected, such conditions emphasized the impact of heat stress on coral holobiont metabolism, without the interference of excessive light.…”
Section: Discussionmentioning
confidence: 95%
“…By the end of the 7-day heat stress event, ambient corals had experienced 2.5 DHW and warm-acclimated corals had experienced 4.5 DHW (conditions classified as "likely" to cause bleaching by NOAA), yet the light levels during the experiment were relatively low (arising from an abnormal period of cloudy weather; Figure 1C). Since temperature and light are synergistic stressors of coral bleaching, it is possible that the low light conditions that prevailed during the experiment alleviated the impact of the 4.5 DHW treatment to some extent (Skirving et al, 2018). While unexpected, such conditions emphasized the impact of heat stress on coral holobiont metabolism, without the interference of excessive light.…”
Section: Discussionmentioning
confidence: 95%
“…The performance of the LSD and DHW indices has been compared for three summertime water temperature anomalies (in 2002, 2004, and 2006), each separated by two years of no anomaly, at the for each of the three years suggested that the better prediction of bleaching severity by the LSD algorithm may be due to the combined use of light and temperature anomalies (Skirving et al 2018). …”
Section: A New Bleaching Prediction Methodsmentioning
confidence: 99%
“…A recent algorithm for the prediction of coral bleaching has been designed to incorporate some of these missing variables, whilst still remaining simple enough to be practically implemented. This algorithm, Light Stress Damage (LSD), incorporates a model of bleaching that includes photosynthetically active radiation (PAR) and temperature, and using this model it attempts to predict bleaching-induced mortality and recovery time following bleaching with increased accuracy (Skirving et al 2018).…”
Section: A New Bleaching Prediction Methodsmentioning
confidence: 99%
See 2 more Smart Citations